Kesalahan Siswa dalam Berpidato Bahasa Inggris - Neni Desi Fajarwati (Indonesian Journal of Applied Linguistics Review, 2017)
This study aimed to analyze the kind of error in English speech of public speaking, to identify the cause of error in English speech of public speaking, and to identify the impact of error in English speech of public speaking. This research conducted in class VIII of Ushuluddin Boarding School South of Lampung. This research employed a qualitative approach and used content analysis as the method of study. A data of the research was 15 documentation record of student’s English speech. To find out the error in students English speech of public speaking, the surface structure taxonomy was used for analyzing of phonology error, and the linguistic category classification and the surface structure taxonomy were used for analyzing of morphology and syntax error.The findings show; (1) the kinds of error in phonology were 156 substitution errors, 136 omission errors and 57 addition errors. Therefore the most dominant error in phonology was substitution error of vowel (102). The total of number errors in morphology and syntax were 169 errors, and the most dominant error in morphology and syntax was diction errors (50). The kinds of error in morphology and syntax were 83 misformation errors, 46 misordering errors, 33 omission errors and 7 addition errors. (2) The cause of error in phonology, morphology and syntax was intra language. Intra language is the error made by the learners in learning English. (3) There are found two impacts of errors in student’s speech; 1) an error in phonology called global error. Global error is makes an utterance difficult to understand. 2) An error in morphology and syntax called local error. Local error is not influence a message of the speech